Growth of long fatigue cracks under non-proportional loadings – experiment and simulation - Y. Hos; M. Vormwald (Fracture and Structural Integrity)
An experimental campaign was carried out on thin-walled tubes under tension and torsion. The results from experiments are measured and compared. It is observed that cracks follow a shear-dominated growth pattern with increasing crack length, instead of a tension-dominated one. The experiments are performed with high amplitudes applied to the specimens, resulting in large cyclic plastic deformations and crack growth rates up to 10-3 mm/cycle. Stress intensity factors were calculated for the proportional loading case.